The dragon's promise eaudiobook - Lim, Elizabeth (Six Crimson Cranes, 2022)
NEW YORK TIMES BESTSELLER • From the critically acclaimed author of Six Crimson Cranes comes the thrilling next adventure! A journey to the kingdom of dragons, a star-crossed love, and a cursed pearl with the power to mend the world or break it... Fans of Shadow and Bone will devour this soaring fantasy. Princess Shiori made a deathbed promise to return the dragon's pearl to its rightful owner, but keeping that promise is more dangerous than she ever imagined. She must journey to the kingdom of dragons, navigate political intrigue among humans and dragons alike, fend off thieves who covet the pearl for themselves and will go to any lengths to get it, all while cultivating the appearance of a perfect princess to dissuade those who would see her burned at the stake for the magic that runs in her blood. The pearl itself is no ordinary cargo; it thrums with malevolent power, jumping to Shiori's aid one minute, and betraying her the next—threatening to shatter her family and sever the thread of fate that binds her to her true love. It will take every ounce of strength Shiori can muster to defend the life and the love she's fought so hard to win.